Diagnosis sitologi tumor venereal menular anjing pada seekor anjing domestik jantan yang belum dikebiri. - Abellisa, Abellisa; Etriwati, Etriwati; Erwin, Erwin; Ajis, Fikri Alsidik (ARSHI Veterinary Letters, 2025)
Canine transmissible venereal tumors (CTVT) are one of the few naturally occurring transmissible cancers in mammals and pose a significant challenge to canine populations worldwide. Transmitted through coitus, this contagious round-cell neoplasm affects the external genitalia of dogs, highlighting the importance of early diagnosis to prevent tumor progression and limit transmission. Cytological evaluation provides a rapid, reliable, and minimally invasive diagnostic approach that enables the definitive identification of CTVT based on its cellular morphology. A two-year-old intact male domestic dog presented with chronic preputial discharge and genital discomfort. Physical examination revealed a reddish, cauliflower-like mass at the base of the penis. Cytological analysis of the preputial exudate revealed numerous round lymphoblast-like cells with a high nuclear-to-cytoplasmic ratio, prominent nucleoli, and frequent mitotic figures, consistent with CTVT. No therapeutic interventions were performed. This case reinforces the value of cytological examination as a diagnostic tool for genital tumors in dogs, facilitating prompt clinical decision-making and supporting disease management in endemic regions.